Radiologic and Functional Evaluation of Electrode Dislocation from the Scala Tympani to the Scala Vestibuli in Patients with Cochlear Implants - Fischer, N. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Localization of the electrode after cochlear implantation seems to have an impact on auditory outcome, and conebeam CT has emerged as a reliable method for visualizing the electrode array position within the cochlea. The aim of this retrospective study was to evaluate the frequency and clinical impact of scalar dislocation of various electrodes and surgical approaches and to evaluate its influence on auditory outcome. MATERIALS AND METHODS: This retrospective single-center study analyzed a consecutive series of 63 cochlear implantations with various straight electrodes. The placement of the electrode array was evaluated by using multiplanar reconstructed conebeam CT images. For the auditory outcome, we compared the aided hearing thresholds and the charge units of maximum comfortable loudness level at weeks 6, 12, and 24 after implantation. RESULTS: In 7.9% of the cases, the electrode array showed scalar dislocation. In all cases, the electrode array penetrated the basal membrane within 45° of the electrode insertion. All 3 cases of cochleostomy were dislocated in the first 45° segment. No hearing differences were noted, but the charge units of maximum comfortable loudness level seemed to increase with time in patients with dislocations. CONCLUSIONS: The intracochlear dislocation rate of various straight electrodes detected by conebeam CT images is relatively low. Scalar dislocation may not negatively influence the hearing threshold but may require an increase of the necessary stimulus charge and should be reported by the radiologist.